Digital Literacy and AI-Based Marketing Training for Startup Entrepreneurs - Chusnul Chotimah; Uswatun Nafi'ah; Nirina Oktafia Anggraini; Razik Irpan Saputra (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Startup entrepreneurs are entrepreneurs who are just starting a business. Startup entrepreneurs need a good understanding of digital technology to manage and market their products. Having good digital literacy is a necessity for running a business in the digital age. Purpose of the Study: The purpose of this community service is to provide digital understanding to 35 entrepreneurs who are member of the Nahdlatul Ulama Scholars Association of Tulungagung Regency and the Business and Technology Incubator of the Faculty of Economics and Islamic Business UIN Sayyid Ali Rahmatullah Tulungagung. Methods: The method used in this service program is to use Participatory Action Research combined with technical training (experience learning). Results: The results of the training and mentoring showed a 13.33% increase in digital literacy understanding. All 35 participants successfully created promotional brochures, despite differences in time and trial success. Participants' satisfaction with the training and mentoring program was satisfactory. The assessment of the impact of the training and mentoring on participants' businesses fell into the "sufficient" category, indicating that participants were beginning to feel the benefits of the program, but the impact was not yet optimal.